2017
DOI: 10.1093/ptj/pzx023
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reproducibility of the STarT Back Tool (Dutch Version) in Patients With Low Back Pain in Primary Care Settings

Abstract: The SBT has been successfully translated into Dutch. The psychometric analysis showed acceptable results and, therefore, the SBT is a valid screening tool for patients with LBP in Dutch primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 42 publications
(84 reference statements)
2
44
3
Order By: Relevance
“…Overall, the proportions and RRs for the STarT Back risk groups in MATCH were comparable to those reported in the original STarT Back validation study by Hill et al at 6-month follow-up (Table 2/Figure 2). The proportions and RRs of those with persistent disabling back pain at 6-month follow-up according to STarT Back risk group in MATCH were also generally similar to those reported in Danish (Morso et al 7 ) and Dutch (Bier et al 20 ) primary care at 3-month follow-up, when accounting for the width of confidence intervals (Table 2/Figure 2). …”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Overall, the proportions and RRs for the STarT Back risk groups in MATCH were comparable to those reported in the original STarT Back validation study by Hill et al at 6-month follow-up (Table 2/Figure 2). The proportions and RRs of those with persistent disabling back pain at 6-month follow-up according to STarT Back risk group in MATCH were also generally similar to those reported in Danish (Morso et al 7 ) and Dutch (Bier et al 20 ) primary care at 3-month follow-up, when accounting for the width of confidence intervals (Table 2/Figure 2). …”
Section: Resultssupporting
confidence: 78%
“…We descriptively compared these estimates with those from 3 prior studies that reported on the predictive validity of the STarT Back risk groups using the same definition of persistent disabling back pain at follow-up (RMDQ ≥7), including the original STarT Back validation study. 4, 7, 20 Next, we examined discrimination by calculating the performance characteristics of the STarT Back categories, applying the same contrasts used in the original STarT Back validation study: contrasting high-risk with low/medium-risk, and contrasting low-risk with medium/high-risk. Last, we examined the external predictive validity of the 3 STarT Back risk groups within 3 subgroups: 1) older adults (age ≥ 65 years), 2) those with acute back pain (<4 weeks duration), and 3) those with self-reported recent major improvement reflecting recovery or near-recovery (those reporting being ‘completely recovered’ or ‘much better’ compared to their index back pain visit, about 2 weeks earlier).…”
Section: Methodsmentioning
confidence: 99%
“…Only one study achieved an internal consistency above 0.9 (strong), which is recommended for use in individuals 101 . Nine studies also assessed the test−retest reliability of the STarT Back with the intraclass correlation coefficient and kappa values ranging from 0.65 to 0.93 (moderate to excellent) 74,75,82,87,98,99,101,103,109 . Construct validity was assessed in ten studies with correlation values ranging from 0.18 to 0.75 (weak to strong); however, most comparisons were of moderate strength 68,71,74,75,79,82,87,98,103,109 .…”
Section: Start Back Toolmentioning
confidence: 99%
“…Face-to-face care During the first face-to-face session, the physiotherapist will tailor the e-Exercise LBP intervention to the patients' identified risk for developing persistent LBP (i.e. low, medium or high), using the Keele STarT Back Screening Tool [29,39,40] (Fig. 1, Table 1).…”
Section: Smartphone Applicationmentioning
confidence: 99%